The Effect of Supplementary Feeding on the Reproductive Performance of Beef Cows in Supporting the Siwab Program - Agung Prabowo; Subiharta Subiharta; Pita Sudrajad; Iswanto Iswanto; Sularno Sularno; Budi Utomo (Program Studi Peternakan, Fakultas Pertanian, Universitas Veteran Bangun Nusantara, 2021)
This study aims to determine the effect of supplementary feeding on the reproductive performance of beef cattle and calf birth weight. Additional feed is given to cows who are pregnant (8-9 months) and after giving birth for 3 months. Additional feed provided is a complete feed prepared from local feed ingredients. The objectives of this supplementary feeding are: maintaining the condition of the mother's body, maintaining normal embryo growth, and accelerating postpartum estrus, as has been done in Megal Village, Pamotan District, Rembang Regency. Provision of additional feed to old pregnant beef cattle (8-9 months) and after giving birth for 3 months in Megal Village, Pamotan District, Rembang Regency. The conclusion of this study is that the provision of additional feed 5 kg / head / day to old pregnant beef cattle and after giving birth for 3 months can reduce the weight loss of beef cattle broods when the availability of feed is limited, increase birth weight of calves and accelerate postpartum estrus. estrus for the first time after childbirth). Provision of additional feed to late pregnant beef cattle and after giving birth is highly recommended, especially in areas where the availability of feed fluctuates.Key words: supplementary feed, reproduction, beef cattle